Professional Baseball Player Type and Geographic Region of Origin Impacts Shoulder External and Internal Rotation Strength - Lori A. Michener; Adam J. Barrack; Bernard Y. Liebeskind; Ryan J. Zerega; Jonathan C. Sum; Ryan L. Crotin; Hillary A. Plummer (International Journal of Sports Physical Therapy)
# Background